Analisis Strategi Penyelesaian Kredit Macet terhadap Kinerja Keuangan Koperasi Simpan Pinjam Semerbak Citra Wangon: Pendekatan Matriks SPACE - Ergita Rahma D; Reifka Nur Amalia; Silfi Dwi Y; Yoiz Shofwa Shafrani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study looks at bad debt resolution strategies and their effect on the financial performance of Semerbak Citra Wangon Saving and Loan Cooperative (KSP) using the SPACE Matrix technique. The financial stability of cooperatives is severely threatened by bad debts, which can reduce liquidity and profitability. The four main dimensions of the SPACE Matrix approach - industry strength (IS), environmental stability (ES), competitive advantage (CA), and financial strength (FS) - were used to evaluate the cooperative's strategic position. The conclusion of the analysis, which places the cooperative in the aggressive quadrant (coordinates 5.00, 2.67), indicates that the cooperative has significant internal strengths and outward growth potential. Some recommended strategies include improved market segmentation, longer loan periods, liability restructuring, and lower interest rates. These strategies are expected to improve the cooperative's long-term financial stability and reduce the likelihood of bad debts.